Multiple primary malignancies for squamous cell carcinoma and adenocarcinoma of the esophagus - Chen, Dongni; Fan, Ningbo; Mo, Junxian; Wang, Weidong; Wang, Ruiqi; Chen, Youfang; Hu, Jia; Wen, Zhesheng (Journal of thoracic disease, 2019)
Patients with esophageal cancer (EC) frequently have multiple primary cancers. We conducted the present study to assess the risk of multiple primary malignancies for patients with squamous cell carcinoma (SCC) and adenocarcinoma (AC) of the esophagus and to investigate the influence of multiple primary tumors on the prognosis of EC patients. Using the data of 44,091 EC patients from the Surveillance Epidemiology and End Results (SEER) database, we calculated the standardized incidence ratios (SIRs) for overall multiple primary cancers and cancers at particular sites among EC survivors. The SIRs of esophageal SCC and AC patients were compared using Poisson regression. The Kaplan-Meier (KM) method was used for survival analysis. Multiple primary cancer risk was significantly increased among both esophageal SCC and AC survivors (SIR: 2.28 and 1.57, respectively; P<0.001). Among SCC patients, the highest SIRs were found in the oral cavity and pharynx (SIR: 16.54), esophagus (SIR: 10.02), and larynx (SIR: 10.34). Also, the highest SIRs following AC cases were observed in the esophagus (SIR: 8.81), stomach (SIR: 9.29), and small intestine (SIR: 4.95). SIRs for the oral cavity and pharynx, lung, and larynx were significantly higher among SCC survivors than AC survivors (all P<0.05). KM analysis revealed no significant difference of overall survival (OS) for multiple primary cancers, including those of the esophagus, stomach, oral cavity and pharynx, and lung among EC patients (log rank =2.04; P=0.564), except for prostate cancer (log rank =96.65; P<0.001). Multiple primary malignancy risk differed by the histological type of esophageal SSC and AC survivor. However, no significant relationship between survival and the multiple primary cancer sites, except for prostate cancer, was observed.